A rare case of spontaneous spinal epidural hematoma with spontaneous resolution - Suman Reddy, P M; Jacob, Jerry; Dsouza, Roger Shannon (Indian Journal of Case Reports, 2024)
Spontaneous spinal epidural hematoma (SSEH) is an uncommon cause of acute spinal cord compression. It is a neurological emergency that requires urgent imaging and appropriate treatment to prevent permanent neurological sequelae. Here, we present the case of a 30-year-old male with no known comorbidities who presented to the emergency department with a history of sudden onset of upper backache and chest discomfort followed by bilateral lower limb weakness. On examination, the blood pressure was 220/120 mmHg, and neurological examination showed decreased tone and power of 2/5 in bilateral lower limbs. In view of the initial chest discomfort, a cardiac evaluation was done, which was normal, followed by magnetic resonance imaging of the whole spine, which showed a lesion in the anterior epidural space suggestive of hematoma, causing spinal cord compression. A final diagnosis was C6-T2 dorsal SSEH secondary to a hypertensive emergency.